A Phenomenological study of home-based caregivers providing palliative care to terminally ill patients at Mahlathi Village, Mopani District, Limpopo Province - Mafuma, Ntwanano Melta (My University, 2024)
Home-based caregivers are a very important part of multidisciplinary teams in the health profession. They work together with health professionals to ease the burden of care on hospitals by providing care to patients in the comfort of their home. However, as they give care, they encounter many challenges that affect the quality of their work. Many studies have been conducted on home-based caregivers. Nonetheless, there are not many that address the motivation and coping strategies that home-based caregivers use to cope with challenges. The current study aimed to explore the lived experiences of home-based caregivers providing palliative care to terminally ill patients in Mahlathi Village, Mopani District, Limpopo Province. A qualitative research approach using a phenomenological design was used. Twelve home-based caregivers (eleven females and one male) aged between 41 and 59 years old were sampled to form part of the study. The participants were selected using a purposive sampling method. Data collection was conducted through semi-structured interviews with the home-based caregivers. The interviews were conducted in Xitsonga and translated into English. The study used interpretive phenomenological analysis (IPA) to analyse the findings. The study revealed that home-based caregivers remain highly motivated to do caregiving work despite the challenges that come with it. Helping community members, personal experiences and a lack of employment were pointed out as the themes. The study further showed challenges and positivity about home-based caregiving. The experiences of the home-based caregivers when working with patients, families of patients, families of the home- based caregivers, community members and institutions where they work were discussed. Psychological experiences of the home-based caregivers and coping mechanisms were also identified. The study concluded that home-based caregivers experience many challenges when caring for terminally ill patients. However, the support from their own families, colleagues, supervisors, and community makes their work easier. It is recommended that the Department of Health set aside time for home-based care programmes to ensure their effectiveness. Increasing home-based caregivers’ salaries to improve on their livelihood should receive attention of the department.
Thesis (M.A.(Clinical Psychology)) -- University of Limpopo, 2024
Keywords: Home-based caregivers; Motivational perceptions; Palliative care; Psychosocial challenges; Coping; Palliative treatment; Terminally ill -- Psychology; Caregivers -- Psychology; Caregivers; Home-based family services